Review of the genus Stenopsyche McLachlan (Trichoptera: Stenopsychidae) in India - Pandher, Manpreet S.; Saini, Malkiat S.; Parey, Sajad H. (Zootaxa, 2013)
With 14 species on record, the genus Stenopsyche McLachlan is reviewed from India. We report variation for 3 previously recorded species, Stenopsyche griseipennis McLachlan, S. dirghajihvi Schmid and S. apiguna Schmid. A catalogue and key for males of Indian species is provided.